Breastfeeding in primary health care: weaknesses and potentialities of nursing care - Zanlorenzi, Gisele Basso; Wall, Marilene; Silva, Marcus Vinicius da Rocha Santos da; Santos, Bruna Piahui dos; Varjão, Jaqueline Alves Soares; Azevedo, Evelin Mayara de Oliveira Silva; Ogradowski, Karin Rosa Persegona (Revista de Enfermagem da UFPI, 2024)
Objective: To identify the weaknesses and potentialities of nursing care for breastfeeding in Primary Health Care (PHC). Methods: A qualitative study developed through workshops held in September 2021 with 43 nursing professionals. Results: Two categories emerged: “Weaknesses of breastfeeding nursing care in PHC” and “Potentialities of breastfeeding nursing care in PHC”. Weaknesses permeate the discourse, which is often not in line with the reality of the postpartum period, lack of theoretical and practical knowledge, cultural influences, short maternity and paternity leave, shortage of professionals, absence of meetings, inappropriate physical space, limited time for care, failure to address the issue and lack of training. Presented as potentialities are the availability of professionals for guidance in different environments, the work of community health agents, the existence of the Women’s, Children’s and Adolescents’ Health Center, the Municipal Breastfeeding Support Network, the use of technology and encouraging the participation of partners from prenatal to postpartum. Conclusion: It is necessary to consider the weaknesses identified in order to develop improvement actions focused on increasing breastfeeding indices. As for the strengths, they reflect successful practices that can support and guide other nursing services.